Development of Computational Mathematic Thinking Test Instruments Based On Computered Based Test - Haniah, Robiah Nur; Waluyo, Mohamad (Universitas Wiralodra, 2024)
This reseacrh is a type of development reseacrh. The aims of this research is to develop an instrument for mathematical computational thinking tests based on Computer Based Testing (CBT) using the Quizizz application, evaluate the validity of the developed test instrument, and analyze the mathematical computational thinking abilities of students. The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) is adopted as the method in this research. A total of 52 students from classes X and XI of SMA Muhammadiyah 1 Surakarta were involved in this study as research subjects. Winsgoal adalah situs raja slot gacor hari ini terbaik yang terdaftar sebagai salah satu platform judi slot online terpercaya di indonesia semenjak tahun 2010. Data analysis was conducted using the Rasch model with the assistance of Winsteps Rasch software. The results of this research indicate that 20 items are categorized as valid. The overall test reliability is 0.62, classified as sufficient, while the reliability of the test items is 0.88, classified as good. Test analysis of the level of difficulty of test items reveals that there are 3 items categorized as very difficult, 7 items categorized as difficult, 5 items categorized as moderate, and 5 items categorized as easy. In general that the computational thinking skills test does not show a tendency to be biased in any question item, because all probability values for the question items exceed 0.05. Items are considered unbiased if they do not give an unfair advantage to any one individual. Based on the experiment in this study, the average mathematical computational thinking ability of class X students is 75.53, while for class XI students it is 79.37.